2020
DOI: 10.3390/w12113108
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tropical Cyclones to Precipitation around Reclaimed Islands in the South China Sea

Abstract: Tropical cyclones (TCs) play an important role in the precipitation of tropical oceans and islands. The temporal and spatial characteristics of precipitation have become more complex in recent years with climate change. Global warming tips the original water and energy balance in oceans and atmosphere, giving rise to extreme precipitation events. In this study, the monthly precipitation ratio method, spatial analysis, and correlation analysis were employed to detect variations in precipitation in the South Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, the effect of the vertical mixing of seawater caused by TCs on the V concentration in Sanya surface waters does not appear significant. In fact, TCs also play a crucial role in the generation of precipitation in the SCS (Yao et al., 2020). Cui et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effect of the vertical mixing of seawater caused by TCs on the V concentration in Sanya surface waters does not appear significant. In fact, TCs also play a crucial role in the generation of precipitation in the SCS (Yao et al., 2020). Cui et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of the vertical mixing of seawater caused by TCs on the V concentration in Sanya surface waters does not appear significant. In fact, TCs also play a crucial role in the generation of precipitation in the SCS (Yao et al, 2020). Cui et al (2022) reported a statistically significant positive correlation between total annual SCS precipitation and the annual number of TCs passing through the SCS.…”
Section: Relationship Between Coral Skeletal V/ca and Tropical Cyclonesmentioning
confidence: 99%
“…Our approach produces distributed rainfall values, which are essential for various applications such as water supply planning, flood management, and disaster preparedness (Yao et al, 2020). In the WNP region, where hundreds of thousands to millions of people are affected by TCs every year, the accurate estimation of distributed rainfall values can aid in the development of effective disaster preparedness plans, including the evacuation of vulnerable communities, mobilization of emergency services, and deployment of relief supplies.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Tropical cyclones (TCs) are one of the world's most destructive natural disasters, bringing heavy rainfall, strong winds, and substantial storm surges that endanger the property and lives of coastal residents [1,2]. They are responsible for 35-50% of the world's extreme rainfall, resulting in catastrophic flooding and natural disasters [3].…”
Section: Introductionmentioning
confidence: 99%